Lex biomedica: concept, nature and ontology - I. V. Ponkin; A. A. Ponkina (Акушерство, гинекология и репродукция)
The article is devoted to the study and explanation of the meaning, nature, structure, features and ontology of extra-legal regulation in the field of healthcare and medicine (lex biomedica). The authors explain the concept and structure of lex biomedica. The article shows other ontological spaces of the bioethical order associated with the lex biomedica normative space; the content of the subject-object area of lex biomedica regulation is described in detail. The article describes and explains the features of the interactions between the space of legal regulation and the space of extra-legal regulation in the field of healthcare. The authors refer to the concept of "bio-law".